Revisiting the future of root canal obturation - James L Gutmann; Vivian Manjarrés; Catalina Méndez De La Espriella (Wolters Kluwer Medknow Publications, 2022)
The techniques for root canal obturation have undergone several changes in the last 10 years. While warm vertical compaction had been the major method of filling the canal, which included the use of core carriers made of structurally stable gutta-percha, recent developments in the manufacturing of precision-tapered, gutta-percha cones and the use of bioceramic root canal sealers have become the clinician's choice in the past few years. The impact of these revolutionary changes is explored with open ended questions and challenges for the reader.